Caregiving-related strain among informal caregivers of older adults with dementia: findings from a nationally representative study - Shubair, Sultan A. (Frontiers in Public Health, 2025)
Background and objectivesInformal caregivers (ICs) of older adults with dementia experience caregiving-related physical, emotional, and financial strain. Little is known about their characteristics and caregiving-related strain differences by dementia status.Research design and methodsA cross-sectional study was implemented among probable, possible, and non-dementia ICs of older adults from the 2017 National Health and Ageing Trend Study and linked to the National Study of Caregiving data for a nationally representative sample of 2,652. Analysis of variance was used to investigate differences in characteristics and caregiving-related strain by dementia status.ResultsICs of older adults with possible dementia were more likely to report an income ≤99,999 (97.2%, p < 0.001) than ICs of older adults with probable dementia (94.8%) or non-dementia (86.9%), with no other group characteristic observed. Caregiving-related strain varied significantly by dementia status (p < 0.001), with ICs of older adults with probable dementia reporting the highest physical, emotional, and financial strain compared to ICs caring for possible or non-dementia older adults.Discussion and implicationsDementia ICs face disproportionately higher strain and greater financial vulnerability, underscoring the need for targeted interventions such as respite care, financial support, and caregiver training to sustain caregiver well-being as dementia prevalence rises.